CORRELATION BETWEEN PERCENTAGE OF BODY FAT WITH SPEED AND CARDIORESPIRATORY ENDURANCE AMONG FUTSAL ATHLETES IN SURABAYA - Cici Damayanti; Merryana Adriani (Universitas Airlangga, 2021)
Futsal is one of the sport that begin to be popular in Indonesia. Physical condition in futsal is an important aspect because it directly aff ects athlete performance especially for speed and cardiorespiratory. One of the factor that aff ect physical condition is percentage of body fat. The purpose of this study is to analyze the correlation between percent body fat with physical condition of futsal athletes in Surabaya. This study was an observational analytic study with cross sectional design. The population were sixty-eight peoples from members of Buana Mas FC, Garuda Emas FC, Nisrina FC and Surabaya Porprov team 2019. Fifty-four peoples were selected as subject of this study by proportional random sampling method. Data collection included questionnaires for respondent characteristics namely age, occupation, education, smoking history and sports activity, and then, measurement of subcutaneous fat thickness using skinfold calliper, and measuring speed and cardiorespiratory endurance using sprint 20m and yoyo test. Data analyze used Spearman correlation test. The result of this study showed most of respondent have normal percentage of body fat (59.3%). Respondents speed mostly classifi ed as lacking (50.0%) and cardiorespiratory endurance respondents mostly classifi ed as suffi cient (59.3%). The results showed an positive correlation (p = 0.001; R=0.732) between percent body fat with speed, it was mean that the higher percentage of body fat, the slower sprint time. And there was negative correlation (p = 0.001; R=-0.639) between percentage of body fat and cardiorespiratory endurance, so the higher percentage of body fat, the lower cardiorespiratory endurance. This contradictory conclusion is due to increasing sprint time, the respondent speed will decrease while V02Max increase so the cardiorespiratory endurance will increase.